PECULIARITIES OF GENDER IN IDA IN CHILDREN IN THE ARAL SEA REGION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Anemia is a pathological condition characterized by a decrease in the number of red blood cells and hemoglobin per unit volume of blood[1]. It has been established that IDA is the most common disease. According to WHO, about 2 billion people on the globe have iron deficiency (ID), and half of them have it in its extreme form – IDA, which accounts for approximately 80% of all types of anemia [3]. The most vulnerable groups of the population to the development of IDA are young children (under 3 years old), adolescents (mostly girls). It has been shown that the frequency of IDA depends on the geographical, social, and socio-domestic conditions of the population [2]. The most significant causes of iron deficiency in young children are considered to be the increased need of the body for iron due to rapid growth rates and insufficient iron intake from food. A negative iron balance over a long period of time leads to the development of its deficiency in the body, which is accompanied by microcytic, hypochromic, and normoregenerative anemia.